Micromachining of Invar with 784 Beams Using 1.3 ps Laser Source at 515 nm - Hauschwitz, Petr (Materials (Basel), 2020)
To fulfil the requirements for high-resolution organic light-emitting diode (OLED) displays, precise and high-quality micrometer-scale patterns have to be fabricated inside metal shadow masks. Invar has been selected for this application due to its unique properties, especially a low coefficient of thermal expansion. In this study, a novel cost-efficient method of multi-beam micromachining of invar will be introduced. The combination of a Meopta beam splitting, focusing and monitoring module with a galvanometer scanner and HiLASE high-energy pulse laser system emitting ultrashort pulses at 515 nm allows drilling and cutting of invar foil with 784 beams at once with high precision and almost no thermal effects and heat-affected zone, thus significantly improving the throughput and efficiency.